DYNAMIC PERFORMANCE ANALYSIS OF SCISSOR SEAT SUSPENSION SYSTEM - MA MingMing; YU HuiJie; NI WeiYu; WANG HaiHua (Jixie qiangdu)
Based on D' Alembert's principle, the differential equation of the motion about the system was deduced, and the transfer function of the system was obtained by the basis of estabishing virtual equilibrium state of a seat suspension system. The mechanical properties of main components of seat suspension and seat transfer characteristies were obtained by means of experimental measurement. The accuracy of theoretical model was verified by the experimental results. On this basis, the influence of each parameter on resonance frequency and amplitude of the suspension system was discussed. The suspension system was partially improved according to structural parameters. The ideas and methods of this thesis can provide ideas and solutions for seat structure design.